PENGARUH PENDEKATAN PEMBELAJARAN TAKTIS DAN PENDEKATAN PEMBELAJARAN TEKNIS TERHADAP HASIL BELAJAR KETERAMPILAN PASSING DAN STOPING - Ricky Fernando; Kamarudin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This research is about to study the effect of tactical and technical approach to learning result of passing and stoping skill. The results of this study is expected to serve as an alternative solution in order to improve the quality of learning soccer. The method used in this research is the experimental method. The population in this research is the first semester 1 student of FKIP UIR as many as 160 people. The number of samples are 16 people with sampling technique using Cluster Random Sampling. Time of research is for 2 months, the number of treatment 16 times meeting, with frequency 1 week 3 times. The author's chosen instrument is a passing and stoping skills test in football. for physical education students FKIP UIR soccer skills test (early and final test of passing and stoping skills). Based on the result of the analysis, it can be concluded: (1) The learning approach using tactical approach gives influence to the skill of passing and stoping the student of FKIP UIR physical education (2) The learning approach using tactical approach gives influence to the skill of passing and stoping the student of FKIP UIR mask. (3) using a tactical approach and a technical approach are equally influential on passing and stoping skills of UF FKIP students. However, the learning approach using tactical approach has more significant impact than the technical learning approach